Experimental acute myocardial infarction in rats: HIF-1 alpha, caspase-3, erythropoietin and erythropoietin receptor expression and the cardioprotective effects of two different erythropoietin doses - ERCAN, FERİHA (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2013)
The cardioprotective effects of two different doses of erythropoietin administration were analyzed in rats with experimental myocardial infarction. None, saline, standard-dose (5000 U kg(-1)) and high-dose (10,000 U kg(-1)) of human recombinant erythropoietin alpha were administered intraperitoneally in Wistar rats with myocardial infarction induced by coronary artery ligation. Infarct sizes measured after triphenyltetrazolium chloride staining, levels of biochemical markers, histopathology examined by light and electron microscopy, and immunohistochemical expressions of erythropoietin, erythropoietin receptor, hypoxia inducible factor-1 alpha and caspase-3, were analyzed. Lower scores of infarction and hemorrhage, lower number of macrophages and higher score of vascularization surrounding the infarct area were observed in the erythropoietin administered groups (p < 0.05). Erythropoietin administration after myocardial infarction reduced the area of infarction and hemorrhage. There were hypoxia inducible factor-1 alpha and caspase-3 expressions in the marginal area, and erythropoietin and erythropoietin receptor expression in both marginal and normal areas (p < 0.001). Vascularization, erythropoietin expression in the normal area and vascular erythropoietin expression were positively correlated with human erythropoietin levels. The cardioprotective effects of erythropoietin treatment were independent of endogenous erythropoietin/erythropoietin receptor activity. Moreover exogenous erythropoietin treatment did not suppress endogenous erythropoietin. Erythropoietin administration after myocardial infarction reduced caspase 3 expression (apoptotic activity) and induced neovascularization around the infarct area. Higher erythropoietin administration did not provide an additional benefit over the standard-dose in myocardial protection. (C) 2013 Elsevier GmbH. All rights reserved.
Keywords: Erythropoietin; Erythropoietin receptor; Caspase 3; Hypoxia inducible factor 1 alpha; Myocardial infarction; Rat; ISCHEMIA-REPERFUSION INJURY; ISCHEMIA/REPERFUSION INJURY; DEPENDENT PATHWAY; PROTECTS; HYPOXIA; BIOLOGY; KINASE; CELLS; NEUROPROTECTION; APOPTOSIS